Expert Views on COVAX and Equitable Global Access to COVID-19 Vaccines - Manriquez Roa, Tania; Holzer, Felicitas; Luna, Florencia; Biller-Andorno, Nikola (International Journal of Public Health, 2021)
Objectives: We face the impossibility of having enough COVID-19 vaccines for everyone in the near future. This study aims to contribute to the debate on equitable global access to COVID-19 vaccines, tackling key ethical discussions and policy challenges regarding COVAX, the global cooperation mechanism for supporting fair vaccine allocation under a distributive scheme. Methods: We conducted in-depth interviews with twelve experts and a literature research on academic articles, media sources and public statements. We built a data analysis matrix and conducted a thematic analysis. Results: Our findings show, first, that interviewed experts who hold different views on vaccine allocation, including moderate nationalist perspectives, agree on joining a global cooperation mechanism. Second, that incentives to join COVAX vary greatly among countries. Third, that specific barriers to COVAX emerged in the early implementation phase. And fourth, that countries might be trapped in a zero-sum game regarding the global vaccine supply. Conclusion: We present findings that enrich early analyses of COVAX, we introduce three ethical discussions that provide a common ground for equitable access to COVID-19 vaccines, and we highlight key policy challenges.